The third mental health revolution: Themes, values and methods of Community Psychology and its relevance in Zimbabwean and African cultural contexts - Maseko, Mpikelelo Mpawusi; Maunganidze, Levison; Mambende, Benjamin; Maphosa, Sibangilizwe (PINS-Psychology in Society, 2017)
Psychology like other progressive scientific disciplines endures constant transformation, with one scientific revolution replacing or superseding another. The nascent field of community psychology represents a paradigm shift, and indeed a mental health revolution in psychology. The paper seeks to illuminate the themes, values, and methods of community psychology. Effort will be made to underscore how the discipline does not attempt to hide behind a “scientific” value free cloak but rather highlight the critical role values play in shaping and informing praxis in psychology and community psychology in particular. The paper also seeks to emphasise that the discipline is relevant in African cultural contexts given the synchronicity between its core values and African cultural values. Finally, an endeavour will be made to examine community psychology in the Zimbabwean context.